PRILAKU KEBERAGAMAAN KELOMPOK JAMAAH TABLIGH DI KOTA GERBANG SALAM (Studi tentang perilaku social dan dakwah keagamaan di Kabupaten Pamekasan) - Supandi, Supandi; rohman, Mujibur (Universitas Islam Madura, 2020)
The preaching pattern of the Tablighi Jamaah Group in the Gate of Salam land has its own charm for researchers to study and research, the aim is to find out in depth about the work patterns of the Tablighi Jamaat in carrying out their da'wah activities, the research method used is to use a qualitative approach with a phenomenological type, informants in This research is about tablighi congregation leaders and members of the public who researchers consider to have knowledge about the tablighi congregation movement. The results of this research are preaching from house to house, making mosques and prayer rooms prosperous. Meanwhile, the objectives of the Tabligh Jamaah group's da'wah on the ground at Gate Salam include: a) Islahunnafsih namely improving oneself from all forms of bad deeds to become good in everyday life, inviting everyone to be close to Allah SWT, namely by inviting other people to be active in ubudiyah activities, namely praying together in the mosque, increasing the amount of dhikr and prayer to the Prophet and even imitating and practicing the deeds carried out by the Prophet's companions through exemplifying the characteristics of the prophet and his companions. and so forth. Harmony between society and the Tablighi Jamaah group in the land of Salam Gate, Harmony between the Tablighi congregation and the Pamekasan district government with the Salam Gate program, according to researchers, there is a connection between one another, because their ideals and desires are the same, namely the realization of an Islamic society.